2022
DOI: 10.1186/s12943-021-01466-9
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR screens uncover protective effect of PSTK as a regulator of chemotherapy-induced ferroptosis in hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is among the most common forms of cancer and is associated with poor patient outcomes. The emergence of therapeutic resistance has hampered the efficacy of targeted treatments employed to treat HCC patients to date. In this study, we conducted a series of CRISPR/Cas9 screens to identify genes associated with synthetic lethality capable of improving HCC patient clinical responses. Methods CRISPR-based loss-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 38 publications
1
50
0
Order By: Relevance
“…It is characterized by dysbalance in the regulation of intracellular iron metabolism and membrane lipid peroxidation ( Ursini and Maiorino, 2020 ). The function of ferroptosis in several types of cancer has been reported previously, including breast cancer ( Li H. et al, 2022 ), hepatocellular carcinoma ( Chen et al, 2022 ), gastric cancer ( Zhang et al, 2021 ), head neck squamous cell carcinoma ( Lu et al, 2021 ), lung cancer ( Li and Liu, 2022 ), renal cell carcinoma ( Du et al, 2021 ), ovarian cancer ( Li H.-W. et al, 2022 ), and pancreatic cancer ( Liu et al, 2021 ). Mou et al (2022 ) has found that for LGG the SAT1 activation is closely related to ferroptosis upon ROS induction.…”
Section: Introductionmentioning
confidence: 69%
“…It is characterized by dysbalance in the regulation of intracellular iron metabolism and membrane lipid peroxidation ( Ursini and Maiorino, 2020 ). The function of ferroptosis in several types of cancer has been reported previously, including breast cancer ( Li H. et al, 2022 ), hepatocellular carcinoma ( Chen et al, 2022 ), gastric cancer ( Zhang et al, 2021 ), head neck squamous cell carcinoma ( Lu et al, 2021 ), lung cancer ( Li and Liu, 2022 ), renal cell carcinoma ( Du et al, 2021 ), ovarian cancer ( Li H.-W. et al, 2022 ), and pancreatic cancer ( Liu et al, 2021 ). Mou et al (2022 ) has found that for LGG the SAT1 activation is closely related to ferroptosis upon ROS induction.…”
Section: Introductionmentioning
confidence: 69%
“…It induces the expression of SLC7A11 in a TEAD-dependent manner and maintains the homeostasis of intracellular GSH, thereby suppressing sorafenib-induced ferroptosis in HCC cells. Inhibition of the antioxidant pathway regulated by YAP/TAZ and ATF4 may resensitize drug-resistant HCC to sorafenib ( Chen et al, 2022 ). In addition, dihydroartemisinin (DHA) can enhance the anticancer effect of sorafenib by downregulating GSH-related proteins in the iron metabolism pathway, thereby enhancing the function of sorafenib in inducing ferroptosis in HepG2 cells ( Cui et al, 2022 ).…”
Section: Ferroptosis and Drug Resistancementioning
confidence: 99%
“…RSL, an inducer of ferroptosis, binds to selenocysteine of GPX4 and inhibits its phospholipid peroxidase activity, thereby triggering ferroptosis, which could be inhibited by GPX4 overexpression ( 54 ). Inhibition of phosphoseryl-tRNA kinase (PSTK), the key enzyme in selenocysteine synthesis, inactivates GPX4 while simultaneously inhibiting GSH biosynthesis, inducing ferroptosis ( 65 ). It has been shown that over physiologic concentrations of Se upregulate GPX4 transcription, suggesting a role for Se in ferroptosis ( 66 ).…”
Section: Ferroptosismentioning
confidence: 99%